The roles of Jumonji-type oxygenases in human disease. (February 2014) - Johansson, Catrine; Tumber, Anthony; Che, KaHing; Cain, Peter; Nowak, Radosław; Gileadi, Carina; Oppermann, Udo
The iron- and 2-oxoglutarate-dependent oxygenases constitute a phylogenetically conserved class of enzymes that catalyze hydroxylation reactions in humans by acting on various types of substrates, including metabolic intermediates, amino acid residues in different proteins and various types of nucleic acids. The discovery of jumonji (Jmj), the founding member of a class of Jmj-type chromatin modifying enzymes and transcriptional regulators, has culminated in the discovery of several branches of histone lysine demethylases, with essential functions in regulating the epigenetic landscape of the chromatin environment. This work has now been considerably expanded into other aspects of epigenetic biology and includes the discovery of enzymatic steps required for methyl-cytosine demethylation as well as modification of RNA and ribosomal proteins. This overview aims to summarize the current knowledge on the human Jmj-type enzymes and their involvement in human pathological processes, including development, cancer, inflammation and metabolic diseases.